Atypical Manifestation of Crohn’s Disease in a Teenage Girl - E. V. Donskaya; V. P. Gavrilyuk; S. V. Kostin; D. A. Severinov; L. Y. Zakutayeva (Неотложная медицинская помощь)
Crohn’s disease (CD) is nonspecific granulomatous inflammatory disease of all layers of the intestinal wall, characterized by a variety of clinical forms, heterogeneity of age groups of children and extraintestinal manifestations.  The diagnosis of the disease is difficult due to the presence of many  symptoms specific to a number of other surgical diseases of the abdominal cavity organs. This diagnosis is often made intraoperatively. In this study we report a case of treatment of a teenage girl who was admitted with complaints of a mass in the right iliac region extruding above the skin surface, instability of body weight, an increase in body temperature to 37.2° C for one month. As a result of laboratory and instrumental examination, the etiology was not established. Laparoscopy revealed abdominal infiltrate, consisting of the cecum, the distal ileum and a part of the greater omentum, tightly fixed to the anterior abdominal wall, which led to the destruction ofthe peritoneum, muscle tissue and aponeurosis with further infiltration into the sub-cutaneous fat. Appendectomy and separation of the infiltrate were performed. After that, the girl was discharged due to the categorical refusal of the parents of the further treatment.Twelve days later the patient had abdominal pain again, the dynamics of the pain syndrome intensified, the body temperature was febrile. After examination and detection of signs of peritonitis, emergency laparotomy, subtotal resection of the greater omentum, separation of the abdominal infiltrate (repeated), sanitation and drainage of the abdominal cavity were performed. During the surgery, the access to the abdominal cavity was performed with technical difficulties due to the fact that a conglomerate of intestinal loops and omentum was fixed to the anterior abdominal wall from the interior. The conglomerate was separated from the anterior abdominal wall by blunt dissection. The size of the conglomerate was up to 12–15 cm, formed by the transverse colon, the ileum and the greater omentum. The walls of the transverse colon and ileum in the area of the conglomerate had the cartilaginous density. For the purpose of further examination and determination of tactics for further treatment, the child was transferred to the Gastroenterology Department with a diagnosis of “Terminal ileitis. Purulent omentitis. Serous peritonitis. Mild normochromic anemia of mixed origin. Crohn’s disease?” After the additional examination in a specialized hospital, the diagnosis of CD was confirmed.